+0  
 
0
229
1
avatar
Calculate g'(x),where g(x) is the inverse of f(x).
f(x)=x^-3
Guest Mar 6, 2012
 #1
avatar+3077 
0
Samah:

Calculate g'(x),where g(x) is the inverse of f(x).
f(x)=x^-3



f(x)=x^-3=1/(x^3)

2 => 1/8
3 => 1/27

g'(x)=sqrt3( 1/x )

simplified test:
g'( f(x) ) = sqrt3( 1/( 1/(x^3) ) ) = sqrt3( x^3 ) = x
admin  Mar 6, 2012

20 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.